Linderae Radix Ethanol Extract Alleviates Diet-Induced Hyperlipidemia by Regulating Bile Acid Metabolism Through gut Microbiota - Jiang, Tao; Xu, Chuyun; Liu, Huifang; Liu, Muyi; Wang, Minmin; Jiang, Jiarui; Zhang, Guangji; Yang, Chuqi; Huang, Jianbo; Lou, Zhaohuan (Frontiers in Pharmacology, 2021)
Hyperlipidemia is a common metabolic disorder and regarded as one of the main risk factors for cardiovascular disease. The gut microbiota has been identified as a potential contributor to hyperlipidemia as it can greatly regulate bile acid metabolism. Linderae radix is a natural medicine widely used in the treatment of a variety of diseases and is also a common drug for hyperlipidemia. Recently, the lipid-lowering effect of Linderae radix are receiving increasing attention but the underlying mechanism remains unknown. The study aimed to investigate the effects of Linderae radix ethanol extract (LREE) on gut microbiota in rats with hyperlipidemia syndrome. We established a hyperlipidemia rat model using a high-fat diet and used LREE as the intervention. Blood lipid levels and pathological examination were measured to assess the effects of LREE on hyperlipidemia. The gut microbiota was determined by 16s rDNA sequencing and the bile acid metabolism-related proteins were detected by western blot to discover the underlying correlations.The results show that LREE lowered TC, TG, and LDL levels effectively, and it also alleviated liver injury by reducing ALT and AST activity. Meanwhile, LREE improved gut microbiota disturbance caused by HFD via increasing intestinal microbiota diversity and changing the abundance of the Firmicutes, Bacteroidetes, and actinobacteria. In addition, LREE can increase bile acid reabsorption and promote fecal excretion through farnesoid X receptor (FXR), apical sodium-dependent bile acid transporter (ASBT), organic solute transporter alpha (OST-α), and cytochrome P450 family 7 Subfamily A Member 1 (CYP7A1) thus restoring abnormal bile acid metabolism caused by hyperlipidemia.